Pengaruh Layanan Informasi Intraksi Sosial dengan Metode Problem Solving untuk Meningkatkan Penyesuaian Diri Siswa - Afrilia Puspitasari; Rita Sinthia; Mayang T. Afriwilda (UNIVERSITAS BENGKULU, 2024)
ABSTRACT This research aims to describe the influence of information services with social interaction problem solving techniques to improve students' self-adjustment. This research method uses an experimental method with a one group pretest posttest design. The population in this study totaling 148 students. The research sample was taken using a random intact group sampling with a sample size of 28 students. The data collection technique used a self-adjustment questionnaire with a Likert scale. The research data analysis technique uses a t-test (paired sample test show an increase in students' self-adjustment after being given this treatment in the form of information services with techniques problem solving with a value of t = -14.333 with a significance level (2-tailed) of 0.000. This means that there is an influence of information services with social interaction problem solving to improve self-adjustment. Keywords: self-adjustment, information services, problem solving method